2010
DOI: 10.1111/j.1471-6712.2010.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of the experiences of persons with chronic pain in their encounters with the health service

Abstract: Chronic pain causes great suffering for those affected and treating it is one of the most common assignments in the health service. The aim of the study was to investigate the meaning of the experiences of persons with chronic pain in their encounters with health service staff. The study had a descriptive design with a phenomenological approach based on the perspective of caring science. Interviews were carried out with eight patients. The study showed that patients experienced a positive approach and that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 9 publications
4
35
0
9
Order By: Relevance
“…Our findings confirmed the idea that patients do not want to deviate from perceived social norms and be known as an individual who complains a lot (Eriksson et al 2014, Hansson et al 2011. Patients are afraid of being M a n u s c r i p t 23 judged by healthcare professionals when the NRS score they report is perceived as "too high.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Our findings confirmed the idea that patients do not want to deviate from perceived social norms and be known as an individual who complains a lot (Eriksson et al 2014, Hansson et al 2011. Patients are afraid of being M a n u s c r i p t 23 judged by healthcare professionals when the NRS score they report is perceived as "too high.…”
supporting
confidence: 91%
“…In turn, patients have learned from previous reactions of professionals at what NRS score they will be administered a certain analgesic. A study of chronic pain patients also showed that patients have to give an NRS score higher than 5 in order to receive more analgesics from the nurse (Hansson et al 2011). …”
mentioning
confidence: 97%
“…Experiences such as not being listened to, not believed, and not seen as a whole human being are reported (20,21). The importance of receiving a diagnosis was reported in our study and has been found in previous research (22,23).There is a view among patients with chronic pain that a diagnosis of pain symptoms serves as evidence to legitimize their pain (23).…”
Section: Discussionsupporting
confidence: 49%
“…Eccleston, Williams, and Rogers [41] suggested that relationships with HCPs could mediate distress in chronic pain patients, whilst Coulter & Fitzpatrick [42] suggest that patient dissatisfaction may result in reduced adherence to medication. Hansson, Fridlund, Brunt, Hansson, and Rask [43] studied chronic pain patients' experiences of the healthcare system, finding that staff tended to focus upon their areas of expertise, such as medication, potentially ignoring psychosocial difficulties. This theme would suggest that continuing with this strategy is unhelpful for any chronic pain sufferer, regardless of the possible medical aetiology of the pain.…”
Section: Discussionmentioning
confidence: 99%